A comparative study of in vitro antimicrobial, antioxidant and cytotoxic activity of Albizia lebbeck and Acacia nilotica stem bark - Mohammad Tuhin Ali; Sheikh Tanzina Haque; Md. Lutful Kabir; Sohel Rana; Md. Enamul Haque (Bulletin of Faculty of Pharmacy Cairo University, 2018)
Petroleum ether, ethyl acetate and methanol extracts of the stem bark of Albizia lebbeck and Acacia nilotica was investigated for antimicrobial, antioxidant and cytotoxicity assay. The powdered stem bark was extracted successively with petroleum ether, ethyl acetate and methanol solution. The crude extracts were subjected to antimicrobial, antioxidant and cytotoxicity assay by using disc diffusion method, DPPH and hydroxyl free radical scavenging assay, and brine shrimp lethality test, respectively. The petroleum ether and ethyl acetate extracts of both plants showed the most prominent activity in antimicrobial susceptibility test as compared to methanol extracts. These extracts showed moderate activity against the Bacillus subtilis, Staphylococcus aureus, Vibrio mimicus, Salmonella typhi, Shigella dysenteriae, Candida arrizae and Aspergillus niger. The zone of inhibition against the tested bacteria and fungi were 11–14 mm and 8–10 mm, respectively. The ethyl acetate extract of both plants showed the highest antioxidant and cytotoxic activity when compared with that of petroleum ether and methanol extracts. All the tested extracts showed higher free radical scavenging activity than that of the standard, ascorbic acid. In compared with A. lebbeck, A. nilotica was found to have the lower IC50 value which was 74.29 µg/ml and 68.03 µg/ml in DPPH and hydroxyl free radical scavenging assay, respectively. The LC50 value was 42.36 and 37.32 µg/ml for the ethyl acetate extract of A. lebbeck and A. nilotica, respectively. We suggest further study for the identification of active compounds from the bark extracts of A. lebbeck and A. nilotica.